2001
DOI: 10.1046/j.1526-4610.2001.041007658.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Botulinum Toxin A Injections in the Treatment of Chronic Tension‐type Headache: A Double‐Blind, Placebo‐Controlled Trial

Abstract: In addition to vascular and supraspinal influences, contraction of craniofacial muscles or central sensitization processes following continuous nociceptive input of craniofacial muscles may play an important role in the pathogenesis of tension-type headache. Chemodenervation induced by botulinum toxin injection is successfully used to decrease muscle tension. If muscle tension is important in this type of headache, then botulinum toxin could be helpful in its treatment. We conducted a randomized, placebo-contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
2
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(79 citation statements)
references
References 18 publications
(28 reference statements)
1
72
2
4
Order By: Relevance
“…A long list of studies, which cannot be discussed here, represent "pro" and "cons" factions [29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Bont-a In Headache Treatmentmentioning
confidence: 99%
“…A long list of studies, which cannot be discussed here, represent "pro" and "cons" factions [29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Bont-a In Headache Treatmentmentioning
confidence: 99%
“…With respect to CTTH, Schmitt et al [13] performed a double-blind, placebo-controlled, randomised study in which BTX-A injections conferred a slight benefit to patients with CTTH for affective variables at the first month as determined by the West Haven-Yale multidimensional pain inventory (WHYMPI). However, pain reduction, analgesia intake and activity level did not differ between BTX-A and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this study demonstrated a significant placebo response, which may suggest psychological factors could play a role in this condition. Schmitt et al suggest individualised patient therapeutic regimens with repeated injections may provide most benefit [13].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the therapeutic effect of pericranial botulinum toxin type A injections, which reduce muscle tone, yielded different results [28]. Schmitt et al [29] demonstrated some improvement in affective variables, but the pain intensity, the number of pain-free days, and the consumption of analgesics, were not statistically different between the groups of patients who received botulinum toxin and placebo. Rollnik et al [30,31] did not find any beneficial effect of botulinum toxin compared with placebo despite some objectively recorded reduction in resting muscle activity.…”
Section: Pathophysiological Hypothesesmentioning
confidence: 99%